Unravelling imaginaries of the digital divide among indigenous communities in Taman Negara Malaysia - Abadi, Mansurni (Digital Theory, Culture & Society, 2024)
The digital divide is frequently conceptualized as a disparity between those who possess access to contemporary technologies and those who lack such access. This divide is often defined by factors such as physical access, technological proficiency, and disparate outcomes. However, this perspective frequently neglects its historical origins in the "development" discourse, which has been shaped by global and local telecommunication policies. The recent initiatives to enhance digital access in "remote" regions, such as Malaysia, prompt a reassessment of regional discourses on digital inequality. This study examines the ways in which indigenous groups, particularly the Batek and Semokberi communities in Taman Negara National Park (spanning Pahang, Kelantan, and Terengganu in Malaysia), experience and interpret information and communication technologies (ICTs). For these communities, the use of information and communication technologies (ICTs) is a relatively recent phenomenon. This paper employs the concept of spatial imaginaries to examine how digital access shapes perceptions of social categories like "connected" and "disconnected." The findings reveal that the digital divide is not merely a matter of access; rather, it is actively constructed through institutional and community narratives about how connectivity reshapes spatial and temporal experiences, influencing broader discussions on digital inclusion.